Modulation of the Thrombin Pathway Restores LTP in a Pilocarpine Mice Model of Status Epilepticus - Shavit-Stein, Efrat; Berkowitz, Shani; Davidy, Tal; Fennig, Uri; Gofrit, Shani Guly; Dori, Amir; Maggio, Nicola (Frontiers in Cellular Neuroscience, 2022)
Background Status epilepticus (SE) leads to memory impairment following a seizure, attributed to long-term potentiation (LTP) reduction. Thrombin, a coagulation factor that activates protease-activated receptor 1 (PAR1) is involved in cognitive impairment following traumatic brain injury by reducing hippocampal LTP and in seizures as seen in a SE pilocarpine-induced mice model. Thrombin pathway inhibition prevents this cognitive impairment. We evaluated the effect of thrombin pathway inhibition in the pilocarpine-induced SE mice model, on LTP, hippocampal, and serum markers for inflammation, the PAR1 pathway, and neuronal cell damage. Methods SE was induced by injecting C57BL/6J mice with pilocarpine. Before pilocarpine injection, mice were injected with either the specific thrombin inhibitor α-NAPAP [Nα-(2-naphthalene-sulfonylglycyl)-4-amidino-DL-phenylalaninepiperidide], the PAR1 antagonist SCH79797, or vehicle-only solution. Recordings of excitatory postsynaptic potentials (EPSP) were conducted from hippocampal slices 24 h following pilocarpine injection. Hippocampal real-time PCR for the quantification of the PAR1, prothrombin, and tumor necrosis factor α (TNF-α) mRNA expression levels was conducted. Serum levels of neurofilament light chain (NfL) and TNF-α were measured by a single molecule array assay. Results The EPSP was reduced in the pilocarpine-induced SE mice (p < 0.001). This reduction was prevented by both NAPAP and SCH79797 treatments (p < 0.001 for both treatments). Hippocampal expression of TNF-α was elevated in the pilocarpine-induced SE group compared to the control (p < 0.01), however, serum levels of TNF-α were not changed. NfL levels were elevated in the pilocarpine-induced SE group (p = 0.04) but not in the treated groups. Conclusions Pilocarpine-induced SE reduces LTP, in a thrombin PAR1-related mechanism. Elevation of serum NfL supports neuronal damage accompanying this functional abnormality which may be prevented by PAR1 pathway modulation.